Transformasi Perkembangan Tafsir: Model Tafsir Hadis Modern Fazlur Rahman Sebagai Kritik Terhadap Model Tafsir Sebelumnya - Ananda, Annisa Rizki; Masruchin, Masruchin (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2021)
AbstractThis paper discusses about the transformation of the development of interpretation which was initiated by a modern commentator from Pakistan named Fazlur Rahman where he tried to restore the position of hadith which was considered to have stagnate and died in the growth of its interpretation. Fazlur Rahman offers a new method in increasing the growth of hadith science to be more developed and able to answer modern contexts with more complex problems. The purpose of this study is to reveal Fazlur Rahman's thoughts on hadith which are considered controversial but in fact have a very good purpose for the position of hadith it self, and to reveal the hadith research methods offered by Fazlur Rahman as a modern method in the science of hadith. This study uses the library research method and the results of the study found that the hadith method offered by Fazlur Rahman is a socio-historical method.AbstrakTulisan ini mengkaji tentang transformasi perkembangan tafsir yang digagas oleh seorang mufassir modern asal Pakistan bernama Fazlur Rahman dimana ia mencoba untuk mengembalikan kedudukan hadis yang dianggap mengalami stagnasi dan mati dalam pertumbuhan tafsirnya. Fazlur Rahman menawarkan metode yang baru dalam meningkatkan pertumbuhan ilmu hadis menjadi lebih berkembang dan dapat menjawab konteks modern dengan permasalahan yang lebih kompleks. Tujuan dari penelitian ini adalah untuk mengungkap pemikiran Fazlur Rahman mengenai hadis yang dinilai kontroversional namun pada kenyataannya memiliki tujuan yang sangat baik bagi kedudukan hadis itu sendiri, serta mengungkap metode penelitian hadis yang ditawarkan Fazlur Rahman sebagai metode modern dalam ilmu hadis. Penelitian ini mengunakan metode library Research dan hasil penelitian ditemukan bahwa metode hadis yang ditawarkan oleh Fazlur Rahman adalah metode sosio-historis.Kata Kunci: Fazlur Rahman; Metodologi Hadis; Pemikiran Modern.